LONG HISTORY OF CORPORATE SOCIAL RESPONSIBILITY (CSR) - Bahri, Syamsul (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
The concept of Corporate Social Responsibility (CSR) or Corporate Social Responsibility is a concept that positions companies as part of society. Companies do not only pursue economic benefits for owners, directors and employees, but must have an impact on the socio-economic community and environmental improvement. Before the concept of CSR existed, the practice of corporate social responsibility had been implemented by Andrew Carnegie (1835-1919) the founder of the Carnegie Steel Company in 1870. Andrew Carnagie built philanthropy by establishing a local library, helping create world peace, and funding research activities. In a global context, the term CSR has been used since the 1970s and has become increasingly popular, especially after the publication of the book Cannibals with Forks: The Triple Bottom Line in 21st Century Business (1998) by John Elkington. Developing 3 important components of sustainable development, namely economic growth, environmental protection, and social equity initiated by the World Commission on Environment and Development (WCED) in the Brundtland Report (1987), Elkington developed the concept of the CSR program into three: namely 3P (profit , planets, and people). Besides reaping success, CSR has also experienced failure. The basic concept of CSR was also developed into Corporate Social Leadership (CSL). Indonesia began to recognize the concept of CSR since the 1980s and has become increasingly popular since Law no. 40 of 2007 concerning Limited Liability Companies.